Epigenetics meets proteomics in an epigenome-wide association study with circulating blood plasma protein traits - Shaza B. Zaghlool (Nature Portfolio, 2020)
DNA methylation is associated with complex traits and the expression of genes and proteins. Here, Zaghlool et al. perform epigenome-wide association studies for 1,123 plasma proteins, replicate obtained protein (p)QTMs in an independent cohort and find overlap of pQTMs with expression QTMs and previously reported disease associations.